Perancangan Hotel Resort di Kawasan Wisata Pantai Hoya dengan Pendekatan Arsitektur Neo-Vernakular - Simorangkir, Rechey Ibrahim; Saraswaty, Rina (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2024)
This article or writing aims to develop tourism in the Nias Islands, especially Hoya Beach. The Nias Islands offer interesting nature and culture, but the number of visits on weekdays is lower than weekends and holidays. Therefore, it is necessary to build supporting facilities, such as hotels and resorts, to increase tourist attraction. Hotels and resorts at Hoya Beach will adopt a Neo-Vernacular Architecture approach to showcase the unique culture of Nias. The aim is to support the development of Hoya Beach as a major tourist destination that contributes to the economic growth of the Nias Islands. By designing comfortable and attractive accommodation facilities, Hoya Beach has the potential to become one of the most popular tourist destinations in Indonesia and provide economic benefits for the local community.